Preparation of semiconductor light-emitting nanoparticles with long-term storage and transport stability
By dissolving and diluting the semiconductor luminescent nanoparticle dispersion, nanoparticles in the form of paste were prepared, which solved the problems of stability and solubility during storage and transportation, and achieved long-term stability and convenient transportation.
Patent Information
- Application Number
- CN202411561366.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, semiconductor luminescent nanoparticles are prone to aggregation, deterioration of dissolution ability and degradation of material quantum efficiency during storage and transportation, resulting in poor optical characteristics and stability.
Using a preparation method, the semiconductor luminescent nanoparticle dispersion is dissolved in a non-polar solvent to form a mixture, and then diluted with a polar solvent to precipitate the nanoparticles. After centrifugation, nanoparticles in the form of paste are obtained, which are retained. The amount of solvent does not exceed 50% by weight of the total weight.
The long-term storage stability of semiconductor luminescent nanoparticles is achieved and easy to transport, the stability of photoluminescent performance and solubility is maintained, and aggregation and degradation is avoided. It is suitable for storage for more than 30 days.
Smart Images

Figure CN119432381A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing semiconductor luminescent nanoparticles with long-term storage and transportation stability. The method can solve the problems of aggregation, deterioration of solubility and decrease in material quantum efficiency of semiconductor luminescent nanoparticles over time in the prior art. Background Art
[0002] Semiconductor luminescent nanoparticles (SNPs) are emerging as a promising material for a variety of applications including lighting applications, microelectronics, displays, and medical imaging. SNPs are typically between 1 and 10 nm in size and emit light in the visible spectrum from 400 to 650 nm. Due to their small size, which leads to quantum confinement, SNPs have many advantages, including narrow emission peaks, large absorption cross-sections, high quantum yields, the ability to precisely control the luminescence properties, and the potential for additional chemical modifications. Quantum rods (QRs), a specific type of SNPs with anisometric (rod-like) shape, have higher luminescence efficiency, longer lifetime, linearly polarized PL emission, and better light output coupling efficiency with less self-absorption, making them very promising candidates for LED down-conversion materials that can be used in displays and general lighting.
[0003] In lighting applications, these SNPs can be used to create efficient and tunable light sources. For example, by combining SNPs with blue LEDs, white light with a high color rendering index (CRI) can be produced, which is important for applications such as indoor lighting. SNPs can also be used to produce light with specific spectral properties, such as narrow-band emission or a specific color temperature. In displays, the use of SNPs is being explored as a replacement for traditional phosphors in LCD backlights. By using SNPs instead of phosphors, a wider color gamut and higher color saturation can be achieved, resulting in more vivid and realistic images. SNP-enhanced displays are also more energy-efficient, requiring less power to produce the same brightness as traditional displays.
[0004] SNPs have several important optical properties that are primarily used to classify materials and standardize their commercial uses. The most important properties of SNPs are the emission wavelength, full width at half maximum (FWHM), and photoluminescence quantum yield (PLQY). PLQY refers to the efficiency of the SNP in converting absorbed photons into emitted photons. It is expressed as a percentage, and the higher the value, the higher the efficiency. Quantum efficiency is an important parameter for SNPs in lighting and display applications because it determines the brightness and color purity of the emitted light. SNPs with high quantum efficiency are preferred for these applications because they can produce brighter and more vivid colors.
[0005] The full width at half maximum (FWHM) refers to the width of the spectral peak of the SNP emission spectrum at half of its maximum intensity. It is a measure of the color purity of the emitted light. SNPs with narrower FWHM can produce light with more precise wavelengths, so that the resulting spectrum can be more accurately adjusted. In lighting and display applications, SNPs with narrower FWHM are preferred to produce high-quality, accurate colors.
[0006] In addition to the PL properties, the solubility of SNPs is also a very important parameter. In particular, due to their natural ligands (ligands from NP synthesis), SNPs are usually soluble in non-polar solvents such as hydrocarbons (hexane, toluene, etc.). However, over time, the solubility of SNPs will gradually decrease due to desorption of ligands, surface oxidation and particle aggregation. This makes the resulting solution useless in most applications, as usually SNPs are solution processed, so the solubility and PL properties of SNPs are equally important and should remain stable when the material is stored and transported.
[0007] The stability of SNPs is characterized by the fact that the above optical properties and solubility deteriorate over time when exposed to external influences such as heat, oxygen and moisture. A major obstacle to the widespread use and integration of SNP-based electronic products is the degradation of the material during storage and transportation. A common practice for storing and transporting SNPs is to dissolve the material in an organic solvent such as toluene or hexane. However, since most organic solvents are highly flammable, this method has potential safety hazards because a large amount of solvent is required to store the material in batches. In addition, the flammability of the solvent poses a major obstacle to transporting the material overseas for commercial and research purposes. Another technique for transporting SNPs is to completely dry the material and store it in powder form. However, using this method, the material will undergo irreversible aggregation over time, resulting in a decrease in solubility and material quantum efficiency.
[0008] One prior art mixes a (meth)acrylate-based monomer with a surface-modified quantum dot (QD). The quantum dot is surface-modified with two ligands. The content of the quantum dot is 1 to 60 wt% based on the total weight of the solvent-free quantum dot composition, and the viscosity is 30 cps or less. The quantum dot composition is used for inkjet printing. The storage stability of the quantum dot composition is measured by the viscosity change within 4 weeks. However, the patent does not describe the stability of the optical properties of the quantum dots (such as photoluminescence quantum yield or emission wavelength) over several weeks.
[0009] Another prior art discloses the preparation of a quantum dot dispersion in a branched aliphatic hydrocarbon. It is a QD solvent dispersion with a viscosity of about 0.5–3C at 40°C. The dispersion consists of 5% to 95% of different solvents relative to 100wt% QD dispersion. The stability of the quantum dot dispersion was evaluated by measuring the difference in transmittance in different solvents over a period of one month. The presence of agglomeration at different quantum dot concentrations in different solvents was also introduced. However, the difference in the optical properties of quantum dots in solvent dispersions over a period of time was not studied. Therefore, the patent does not explore the long-term stability of quantum dots and their optical properties.
[0010] Another prior art prepares a gel adhesive modified with graphene quantum dots for electrode conductive applications. The paste gel is synthesized by mixing graphene quantum dots with ion-conducting polymer monomers and initiators. The process patent does not mention the storage stability of quantum dots, and the preparation of the gel is only applicable to graphene quantum dots.
[0011] Another prior art proposes a solid carbon quantum dot material having the advantages of high fluorescence intensity, good color stability and good dispersibility. The material is prepared by dispersing carbon quantum dots in a specific dispersant. The size difference of the carbon quantum dots was measured after storage at high temperature for 30 days. However, the subsequent change in the emission wavelength of the quantum dots was not described. In addition, the study did not study the changes in fluorescence quantum yield and other optical properties during storage at room temperature. In addition, the process patent only applies to carbon quantum dots and not to any other light-emitting semiconductor nanoparticles.
[0012] Another prior art produces a perovskite quantum dot powder for long-term storage stability of nanoparticles. The quantum dots are spray dried and calcined to form a powder. In addition to the long-term stability of the optical properties, the application also describes the convenience of storage and transportation of the material in powder form. However, the patent does not explore the possibility of agglomeration and dispersion quality changes over a certain period of time. In addition, the uniformity of brightness within 3 weeks (500 hours) is analyzed, but other optical properties such as photoluminescence quantum yield during long-term storage are not analyzed. This process patent only applies to perovskite quantum dots and not to any other light-emitting semiconductor nanoparticles.
[0013] Therefore, in order to solve the deficiencies in the prior art, the present invention proposes a method for preparing semiconductor luminescent nanoparticles that can achieve long-term storage stability and are easy to transport. Summary of the invention
[0014] The present invention provides a method for preparing a stable semiconductor light-emitting nanoparticle (SNP) material (such as quantum dots and quantum rods) suitable for long-term storage and transportation, wherein the SNP material is in the form of a paste, wherein the amount of residual solvent does not exceed 50wt% of the total weight of the paste. The method comprises: preparing a nanoparticle dispersion and dissolving it in a non-polar solvent to form a nanoparticle dispersion mixture; transferring the mixture to a container for storage and / or transportation applications; diluting the mixture in the container with a polar solvent miscible with the non-polar solvent to precipitate the nanoparticles; centrifuging the container containing the precipitated nanoparticles to separate the solid and the liquid; discharging the liquid from the container to obtain semiconductor light-emitting nanoparticles in the form of a paste, wherein the amount of the residual solvent mixture contained in the paste does not exceed 50wt% based on the weight of the paste. The paste can be stably stored and conveniently transported in a closed vial. The paste contains the SNP material and the residual solvent, ensuring the long-term stability of the material. The paste can be stored for more than 30 days without any deterioration in photoluminescent properties and solubility, and is very easy to transport due to the low concentration of flammable solvents.
[0015] Preferably, the semiconductor light-emitting nanoparticles have a core-shell or core-multi-shell structure.
[0016] Preferably, the semiconductor luminescent nanoparticles belong to group AIIBVI.
[0017] Preferably, the semiconductor light-emitting nanoparticles include a material selected from the following group: CdSe, CdS, ZnSe, ZnS.
[0018] Preferably, the semiconductor luminescent nanoparticles belong to group AIIIIBV.
[0019] Preferably, the semiconductor light-emitting nanoparticles contain InP in their structure.
[0020] Preferably, the semiconductor light-emitting nanoparticles are selected from the following groups: CdSe / CdS, CdSe / Cd x Zn 1-x S, CdSe / CdS / Cd x Zn 1-x S, CdSe / CdS / ZnS, InP, InP / ZnS, InP / ZnSe, InP / ZnSe / ZnS or perovskite-type materials, wherein x is in the range of 0.01-0.99. .
[0021] Preferably, the non-polar solvent is an aliphatic or aromatic hydrocarbon compound or a mixture thereof.
[0022] Preferably, the aliphatic hydrocarbon compound is selected from hexane, octane, ethyl acetate, heptane, chloroform, diethyl ether and a mixture thereof.
[0023] Preferably, the aromatic hydrocarbon compound is selected from toluene, 1,2-dimethylbenzene, 1,3-dimethylbenzene, 1,4-dimethylbenzene, ethylbenzene, and mixtures thereof.
[0024] Preferably, the polar solvent is selected from methanol, ethanol, propanol, isopropanol, acetone, acetonitrile, ethyl acetate, dimethylformamide, and mixtures thereof.
[0025] Preferably, the semiconductor luminescent nanoparticle paste exhibits stable characteristics for more than 30 days in terms of photoluminescence quantum yield, emission wavelength, half maximum full width and dissolution characteristics.
[0026] Preferably, the quantum yield difference of the semiconductor luminescent nanoparticle paste during the entire storage period is less than 5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Shown are the absorption spectra of the initial (fresh) paste sample and the paste sample after 34 days of storage.
[0028] Figure 2 Shown are the photoluminescence spectra of the initial (fresh) paste sample and the paste sample after 34 days of storage. Specific embodiments
[0029] This embodiment illustrates a method for preparing semiconductor light-emitting nanoparticles, which is synthesized in a batch reactor apparatus using a solvothermal method together with necessary precursors. Depending on the composition of the final material, these precursors can include alkyl carboxylates of the desired metal (e.g., cadmium oleate, zinc oleate, indium oleate, copper acetate, lead acetate, cesium oleate), inorganic salts (PbCl2, PbBr2, PbI2, CdCl2, ZnCl2, CdSO4), and various sulfur-containing compounds (e.g., Se-ODE, S-ODE, trialkylphosphine selenide, trialkylphosphine sulfide, elemental selenium and sulfur, thiourea, selenourea, dithiocarbamate, selenophene).
[0030] The synthesis process is usually carried out in the temperature range of 200 to 380 ° C, or at room temperature. Injection methods or direct heating of the precursor method can be used. Nanocrystals obtained by these methods include luminescent nanoparticles such as CdSe, CdS, ZnSe, ZnS, InP, perovskite nanoparticles (CsPbCl3, CsPbBr3, CsPbI3, FAPbBr3, MAPbBr3 and their mixed halide analogs), CuInS2, and their core-shell and alloy counterparts, such as CdSe / CdS, CdSe / Cd x Zn 1-x S, CdSe / CdS / Cd x Zn1-x S, CdSe / CdS / ZnS, InP, InP / ZnS, InP / ZnSe, InP / ZnSe / ZnS, InP / ZnSe x S 1-x , CuInS2 / ZnS, CuInS2 / ZnSe / ZnS, CuInS2 / ZnSe x S 1-x , where x is in the range of 0.01-0.99. Nanoparticles can take on various shapes, such as polyhedral spheres, rods, tetrapods, pyramids, cubes, dumbbells, platelets, disks, or irregular shapes.
[0031] In most methods for synthesizing semiconductor nanocrystals, nonpolar surfactants (coordinating ligands) are used to control the growth of nanoparticles and ensure their solubility in the reaction mixture. These surfactants include alkyl carboxylic acids (such as oleic acid), alkyl amines (such as oleylamine, dodecylamine), alkyl phosphonic acids (such as hexadecylphosphonic acid, hexylphosphonic acid), trialkyl phosphines (such as trioctylphosphine, tributylphosphine) and trialkyl phosphine oxides, which can also be used as ligand shells and have high solubility in traditional nonpolar solvents.
[0032] After synthesis, the reaction mixture is usually diluted with a non-polar solvent for purification. These luminescent nanoparticles have various luminescence properties, such as photoluminescence quantum yield (PLQY), emission peak full width at half maximum (FWHM), emission maximum wavelength (λ max). The stability of these properties over time depends on factors such as the oxidation rate, interaction with water and oxygen in the air, the stability of the ligand molecules, and their attachment to the nanoparticle surface. Issues such as ligand detachment, rearrangement, or degradation can compromise solubility in traditional solvents, thereby affecting the luminescent properties of the material and its suitability for device fabrication. Uniform distribution of nanomaterials is critical for finished devices such as: polymer films for displays, emissive layers in QLED electroluminescent devices, or absorber layers for solar cells. This cannot be achieved if nanoparticle solubility is compromised. Given that the achievable concentration of semiconductor nanoparticles in solvents is typically limited to less than 50 g / L, storage of large quantities in solution poses challenges due to the flammability and toxicity of typical non-polar organic solvents. Therefore, for storage and transportation, a dry powder form is often preferred. However, maintaining the stability of luminescent properties and solubility in this form presents significant challenges. To address these issues, we present a process for purifying semiconductor light-emitting nanoparticles to facilitate long-term storage and transportation. The process includes transferring the nanoparticle dispersion to a storage / transportation container, diluting the nanoparticle dispersion with a polar solvent miscible with the non-polar solvent in the dispersion to precipitate the nanoparticles, centrifuging the container to separate solid and liquid components, and finally draining the liquid to obtain semiconductor light-emitting nanoparticles in the form of a paste. The paste contains semiconductor light-emitting nanoparticles and no more than 50wt% of residual solvent based on the total weight of the paste, which can be stored for a long time without affecting its performance.
[0033] The non-polar solvent used in the SNP purification process can be an aliphatic or aromatic hydrocarbon compound or a mixture thereof. The non-polar solvent can be a single or branched or non-aromatic hydrocarbon. Some examples of aliphatic hydrocarbon compounds include, but are not limited to, hexane, octane, ethyl acetate, heptane, chloroform, ether, and mixtures thereof. Examples of aromatic hydrocarbon compounds include, but are not limited to, toluene, 1,2-dimethylbenzene, 1,3-dimethylbenzene, 1,4-dimethylbenzene, ethylbenzene, and mixtures thereof. The non-polar solvent is added to the prepared nanoparticles, and the nanoparticles are completely dissolved with or without the help of ultrasound. The SNP product is then separated from any desired byproducts by a multiple process of precipitation, centrifugation (filtration), and redispersion. Further, the nanoparticles are precipitated from the mixture of nanoparticles and the non-polar solvent using a polar solvent. The polar solvent includes, but is not limited to, the following: methanol, ethanol, propanol, isopropanol, acetone, ethyl acetate, acetonitrile, dimethylformamide, and mixtures thereof. The precipitated semiconductor nanoparticles are separated from the filtrate by centrifugation or filtration, and the filtrate is discharged. The above purification process of precipitation-separation-dissolution is repeated one or two more times as needed to obtain high purity.
[0034] In an exemplary embodiment, after the purification process, the precipitated nanoparticles are dissolved in a non-polar solvent to achieve a liquid state. Subsequently, the dissolved nanoparticles are transferred to a vial made of a corrosion-resistant and sturdy material that can withstand the separation process, such as transparent or amber glass, and with a tightened lid. The vial should also be a suitable container for long-term storage and transportation of semiconductor nanoparticles. The dissolved nanoparticles are precipitated with a polar solvent, and the precipitate is separated from the filtrate. The precipitated paste in the vial consists of purified semiconductor nanoparticles and a residual solvent mixture of varying concentrations. The vial is tightened and sealed with a sealing film to avoid any potential water loss and contamination. The vial was stored at room temperature during the study.
[0035] Test Method
[0036] The long-term stability of the light-emitting semiconductor nanoparticles in the paste is related to the stability of the optical properties during the test. Therefore, the dissolution properties and optical properties such as emission wavelength, full width at half maximum (FWHM) and stable relative photoluminescence quantum yield (PLQY) were measured during the test.
[0037] A small amount of semiconductor nanoparticles from the paste was dissolved in a non-polar solvent to make a test sample with a concentration of 10 g / L. The test sample was then pipetted into a cuvette filled with toluene to measure the emission and absorption spectra. Pre-analyzed semiconductor nanoparticles with known and established optical properties were used as references for PLQY measurements. After the initial two measurements, two weeks later, three measurements were performed on the test sample and the reference sample to standardize the results. The PLQY relative to the reference material was calculated using the following formula:
[0038]
[0039] in,
[0040] QY s is the PLQY of the test sample
[0041] QY r It is the PLQY of the reference
[0042] A s is the absorbance of the test sample at the desired wavelength
[0043] A r is the absorbance of the reference at the desired wavelength
[0044] E s is the integrated intensity of the emission spectrum of the test sample
[0045] E r is the integrated intensity of the emission spectrum of the reference
[0046] Sample preparation
[0047] Long-term stability studies were performed using light-emitting semiconductor quantum rods (QRs) with a core and multiple shells. QRs with cadmium selenide (CdSe) seeds were synthesized with cadmium sulfide (CdS) and zinc sulfide (ZnS) shells and cooled for a purification process.
[0048] The reaction mixture is diluted with toluene in a ratio of 1:1 and then centrifuged to remove any undissolved impurities and by-products. Quantum rods are precipitated from the filtrate using isopropanol and methanol in a ratio of 3:1. The precipitated QR is centrifuged and the filtrate is discharged. Toluene is added to the precipitate in a ratio of 1:1 and ultrasonicated to accelerate the dissolution rate. Once the QR material is completely dissolved in toluene, methanol is added to precipitate the material. The mixture is centrifuged and the filtrate is separated from the precipitate containing the QR material and discharged. The purification process of dissolution-precipitation-centrifugation is repeated again to obtain a higher purity product.
[0049] After the purification process, the precipitated quantum rods were dissolved in toluene and half of the solution was transferred to a clean glass bottle. Methanol was added to the vial to precipitate the quantum rods and then centrifuged. Note that the centrifuge speed was reduced accordingly to avoid damaging the glass bottle. The filtrate was discharged from the vial. The precipitate consists of a CdSe / CdS / ZnS quantum rod paste with residual toluene-methanol mixture. The vial was tightened and wrapped in plastic wrap to prevent contamination and moisture loss. The vial was stored in a cool and dry place at room temperature. The remaining half of the material was used as a reference to study the stability of the material when stored in powder form. To this end, the solution was transferred to a clean glass bottle and the solvent was purged using a nitrogen stream at 50°C to obtain a red powder product. The vial was tightened and wrapped in plastic wrap and stored under the same conditions as the paste sample. The emission wavelength of this newly synthesized quantum rod is 617nm, the FWHM is 37nm, and the PLQY is 77%.
[0050] For the test samples, a small amount of the paste in the vial was transferred to a 2 mL vial and the mass of the paste was measured. To maintain a standard concentration of 10 g / L in all test samples, the amount of toluene was adjusted according to the mass of the paste. For example, for 4.3 mg of paste, 0.43 mL of toluene was added to dissolve the material. The material was dissolved without the aid of ultrasound.
[0051] Absorption spectra were measured using a two-in-one deuterium halogen light source jDH-2000, and emission spectra were measured using an OeabtOF-20B series fiber-coupled laser module. Spectra were analyzed and plotted using OriginLab software. In order to more accurately calculate the PLQY, care was taken to keep the absorbance value at 452nm below 0.2 in each measurement. The cuvette was refilled with the reference sample and the test sample for each measurement. The relative PLQY measurements of all new samples were referenced to the previously synthesized red emission QR, and its absolute PLQY was obtained by integrating sphere measurement. In the relative PLQY formula, A r and A s The value is the absorbance value at 452nm. r and Em s The values are measured as the area under the emission spectrum. The optical properties were tested weekly for 34 days to observe any potential differences. A similar protocol was used to evaluate the stability of the quantum rod powder samples.
[0052] Figure 1 and Figure 2 The absorption and photoluminescence spectra of the initial (fresh) paste sample and the paste sample after 34 days of storage are shown, respectively. It is clear that the absorption spectrum of the sample stored on the shelf for 34 days shows all the characteristics of the initial sample. These characteristics include high absorption in the UV range, a shoulder in the blue range, and the first exciton absorption peak around 610 nm. This shows that the optical properties of the material have not changed over time. In addition, there are no observable scattering effects in the aged sample, as indicated by the stable position of the zero line in the absorption and photoluminescence emission spectra. This means that the material has good solubility and dispersibility in organic solvents (toluene) even after 34 days of storage. In addition, the photoluminescence emission spectrum of the aged sample completely overlaps with that of the initial (fresh) sample, indicating no aggregation and degradation after more than a month of storage.
[0053] During the study period, the PLQY calculations and various parameters of the samples stored in paste and powder form were tabulated and are shown below.
[0054] Table 1. Solubility and PL properties of quantum rod paste after long-term storage under normal conditions.
[0055]
[0056] *"+++" means dissolved in less than 1 minute; "++" – dissolved in 5-7 minutes; "+" – dissolved only by sonication; "-" – not dissolved
[0057] Table 2. Solubility and PL properties of quantum rod powders after long-term storage under normal conditions.
[0058]
[0059] *"+++" means dissolved in less than 1 minute; "++" – dissolved in 5-7 minutes; "+" – dissolved only by sonication; "-" – not dissolved
[0060] As can be seen in Table 1, the relative PLQY remained stable from day 1 to day 34. For the first test sample (day 1), the average relative PLQY determined was 84%, while on day 34, the average relative PLQY determined was 88%, a difference of 4% that is within the experimental error (5%) of the PLQY measurement. In addition, the dissolution characteristics of the test samples remained unchanged during the study, where the QR material easily dissolved in the solvent (toluene) without any ultrasonic treatment. The QR material dissolved in toluene in less than 1 minute throughout the period.
[0061] In contrast, as can be seen in Table 2, the PL characteristics of the samples stored in powder form show a gradual decrease in PLQY, from 77% to 50% over the same time period. More importantly, the solubility of the powdered samples dropped significantly, requiring ultrasonic treatment for complete dissolution after 2 weeks, and finally failing to dissolve even after prolonged sonication after about 5 weeks. This renders the material virtually useless, as most applications require solution-processed quantum dot / rod materials.
[0062] It should be noted that the above parameters of the present invention are optimized limitations of the embodiments and should not be interpreted as the only necessary limiting conditions. All modifications and adjustments that do not violate the spirit of the invention are the same or equivalent infringements of the present invention.
[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing semiconductor luminescent nanoparticles with long-term storage and transportation stability, comprising: preparing a nanoparticle dispersion and dissolving it in a non-polar solvent to form a nanoparticle dispersion mixture; transferring the mixture into a container for storage and / or shipping applications; diluting the mixture with a polar solvent miscible with the non-polar solvent in the container to precipitate nanoparticles in the container; centrifuging the container containing the precipitated nanoparticles to separate solids from liquid; and The liquid is drained from the container to obtain semiconductor light-emitting nanoparticles in the form of a paste, wherein the paste contains a residual solvent mixture in an amount not exceeding 50 wt % based on the weight of the paste. The method according to claim 1 , wherein the semiconductor light-emitting nanoparticles have a core-shell or core-multi-shell structure.
3. The method according to claim 1, wherein the semiconductor light-emitting nanoparticles belong to group AIIBVI. The method according to claim 3 , wherein the semiconductor light emitting nanoparticles comprise a material selected from the group consisting of: CdSe, CdS, ZnSe, ZnS. The method according to claim 1 , wherein the semiconductor light emitting nanoparticles belong to group AIIIIBV. The method of claim 1 , wherein the semiconductor light emitting nanoparticles comprise InP in their structure.
7. The method according to claim 1, wherein the semiconductor light-emitting nanoparticles are selected from the following groups: CdSe / CdS, CdSe / Cd x Zn 1-x S, CdSe / CdS / Cd x Zn 1-x S, CdSe / CdS / ZnS, InP, InP / ZnS, InP / ZnSe, InP / ZnSe / ZnS or perovskite type materials, wherein x is in the range of 0.01-0.
99.
8. The method according to claim 1, wherein the non-polar solvent is an aliphatic or aromatic hydrocarbon compound or a mixture thereof.
9. The method according to claim 8, wherein the aliphatic hydrocarbon compound is selected from the group consisting of hexane, octane, ethyl acetate, heptane, chloroform, diethyl ether and mixtures thereof.
10. The method according to claim 8, wherein the aromatic hydrocarbon compound is selected from the group consisting of toluene, 1,2-dimethylbenzene, 1,3-dimethylbenzene, 1,4-dimethylbenzene and ethylbenzene.
11. The method of claim 1, wherein the polar solvent is selected from the group consisting of methanol, ethanol, propanol, isopropanol, acetone, acetonitrile, ethyl acetate, dimethylformamide, and mixtures thereof.
12. The method of claim 1, wherein the semiconductor light-emitting nanoparticle paste exhibits stable characteristics for more than 30 days in terms of photoluminescence quantum yield, emission wavelength, full width at half maximum, and dissolution characteristics.
13. The method of claim 1, wherein the quantum yield of the semiconductor light-emitting nanoparticle paste varies by less than 5% over the entire storage period.